2024
DOI: 10.2903/j.efsa.2024.8521
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of microbiological hazards in food and feed production and processing environments

Konstantinos Koutsoumanis,
Ana Allende,
Declan Bolton
et al.

Abstract: Listeria monocytogenes (in the meat, fish and seafood, dairy and fruit and vegetable sectors), Salmonella enterica (in the feed, meat, egg and low moisture food sectors) and Cronobacter sakazakii (in the low moisture food sector) were identified as the bacterial food safety hazards most relevant to public health that are associated with persistence in the food and feed processing environment (FFPE). There is a wide range of subtypes of these hazards involved in persistence in the FFPE. While some specific subt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 431 publications
(762 reference statements)
0
2
0
Order By: Relevance
“…Studies have shown that CC1 and CC2 are the most prevalent clones in clinical strains, whereas CC9 is often found in food and environmental samples and is a clone with low-virulence [ 19 ]. ST5 and ST121 are known to exhibit higher tolerance to adverse conditions and their capacity to adapt to such environments has been found to be crucial in the formation of biofilms, thereby affecting the persistence of L. monocytogenes in the environment [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that CC1 and CC2 are the most prevalent clones in clinical strains, whereas CC9 is often found in food and environmental samples and is a clone with low-virulence [ 19 ]. ST5 and ST121 are known to exhibit higher tolerance to adverse conditions and their capacity to adapt to such environments has been found to be crucial in the formation of biofilms, thereby affecting the persistence of L. monocytogenes in the environment [ 30 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although previous reports suggested that conveyor belts, centrifugation, and filling operations are not typically significant sources of contamination (EFSA, 2014d). However, there have been reports proving that processing equipment has become an important source of microbial contamination in fruits and vegetables (EFSA, 2024;Snyder et al, 2024). For example, after centrifuging fresh fruits and vegetables, the total natural microbial community in the fruits and vegetables increased by about 1 log unit CFU/g, indicating that the surface of the processing equipment may be a source of microbial contamination and recontamination (EFSA, 2014d).…”
Section: Processing Treatmentsmentioning
confidence: 99%